Severe optochiasmatic arachnoiditis after rupture of an internal carotid artery aneurysm - Ricardo Ramina; Walter O. Arruda; Antônio C. F. Prestes; Mônica K. F. Parolim (Arquivos de Neuro-Psiquiatria)
The case of a 24-year-old man with progressive visual loss due to optochiasmatic arachnoiditis is presented. The cause of the arachnoiditis was subarachnoidal bleeding due to rupture of an internal carotid artery aneurysm. The aneurysm was clipped 5 years after the first episode of bleeding. The diagnosis of optochiasmatic arachnoiditis was confirmed during the operation. This case, is presented in order to discuss the causes, the symptoms and the therapeutical possibilities of this rare condition.